2012
DOI: 10.1007/s11661-012-1530-9
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Precipitation of Alpha2 on Properties and Microstructure in TIMETAL 6-4

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 5 publications
2
22
0
Order By: Relevance
“…It is found that precipitation appears to occur much faster, and more strongly, in a-Ti which is alloyed, very slightly, with V in Ti-6Al-4V than in the pure binary Ti-Al. This is compared to results for Ti-Al-V [21], Ti-Al-Mo [26] and Ti-Al-Zr [27] alloys, where similar ternary alloying effects are observed.…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…It is found that precipitation appears to occur much faster, and more strongly, in a-Ti which is alloyed, very slightly, with V in Ti-6Al-4V than in the pure binary Ti-Al. This is compared to results for Ti-Al-V [21], Ti-Al-Mo [26] and Ti-Al-Zr [27] alloys, where similar ternary alloying effects are observed.…”
Section: Introductionmentioning
confidence: 56%
“…Both Neeraj [19] and Brandes in Ti-7Al wt.% (12Al at.%) [5] observed diffuse spots in TEM, which could be sup-45 pressed by water quenching to provide a fully disordered a-Ti structure. More recently, ordering in the a phase of Ti-6Al-4V has been observed by Wu et al [21] at relatively short ageing times of 35 days at 500 C. In addition, Liew et al [17] studied Ti-9Al wt.% (15Al at.%) by field ion microscopy (FIM) after 500 hours ageing at 650 C and 750 C, where ordering could be observed in the TEM but compositional variations 50 could not. Therefore, the problem of quantifying this precipitation phenomenon has remained strongly intractable to analysis, by 1998-era atom probe tomography instruments (APT) [22,23,24,25], by TEM and by neutron diffraction.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations